(untitled) (Biological Sciences - PJSIR, 2002)
Phosphatic fertili zers are recom mended to be applied as broadcast a nd incorporated i nto th e soil before sowin g._ Mo_re recently application of fertilizer with irrigation water as solution , termed "Fertigation ", has been found equally _effective for wheat production . Fertilizer zinc whose requirement i s small and is commonly deficient in soils, was tried as _tert1gatt on m order to determine its effect on yield and P use efficiency by wheat. Single superphosphate fertilizer was applied at 22 and 44 kg P ha·1 either ·alone or with 1O kg Zn ha·1. The method of application employed was broadcast at sowing and fert1gat10n at first irrigation . It was found that rate of P application increa sed wheat grain yield over control and P applied @_ 44 .kg h a·1 by fertigation proved significan tly better than broadcast application. Addition of Zn as broadcast or as fert1gat10n showed no difference in yield compared to P alone. Application of Zn by fertigat,on , however, unproved agronomic and P fertil izer efficiency com pared to its broadcast application at sowing.